Air Pollution: Selected Fuel Stations in Benghazi City, Libya - Najar, Adel; Amajbary, Mohmed A. I; Awarfaly, Abduslam H. A.; Aeyad, Tahani; Bnhmad, Mona H. Ali; Aeyad, Naima; Khalifa, Aliaa M. M. (Scientific Journal for Faculty of Science-Sirte University, 2023)
This study aims to measure the number of pollutants that can be existing in the air of Benghazi city. Twelve refueling stations from different regions of Benghazi City in Libya were selected. The ambient air quality at all stations was investigated. Also, the evaporation of fuels from loosely closed underground tanks has been investigated for two fuel stations. Drager X-am7000 and MiniRAE-3000 Instruments were used to measure the concentration of CH4, H2S, CO, O2, xylene, and benzene as pollutants in the atmosphere. The pollutant concentrations were within the range of the FEPA air quality standard in most stations; however, the measurement of these pollutants during tank refueling showed a high percentage in the surrounding area of the fuel tanks. Therefore, this study can contribute to understanding air pollutants exposure and its effects on human health.